Ultrasonic testing of heat damaged composite materials - Cheah, Wai Chuen (2015)
Lightning damage in composite specimens can be simulated by heating a composite specimen with a heat gun to high temperatures. As a result, delamination may occur at various layers in composite. This report presents the study of the temperatures at which delamination starts to occur in different composite materials. The sensitivity of different Non-Destructive Testing (NDT) techniques of Ultrasonic Testing and Thermography on heat-treated composite materials would also be discussed. In this report, Heating, Ultrasonic Tests and Thermography were conducted on different samples of Carbon Fibre Reinforced Polymer (CFRP). The composite specimens will be heated by the heat gun for a time interval of 35 minutes. The process is repeated with different temperatures, maintaining the time interval. The procedure of heat damage on the composite specimens will follow close to the work done by Haridas. Ultrasonic Testing and Thermography will then be conducted to determine the extent of the damaged areas. This report will present the results obtained from Visual Inspection, Ultrasonic C-Scan and Thermography. The objective of the report is to determine the amount of heat required to damage the composite specimens. The internal damage results would also be compared with external visual damage due to the heat to determine correlations between the two. Attempts to correlate the heat resistivity of the composite specimens with temperature would also be discussed. Future work could involve proposing damage fracture growth mechanisms which have not been widely reported in the literature.